A Systematic Review of Research Trends in Methane Emissions from Rice Fields in Asia - I Gusti Ayu Agung Pradnya Paramitha (LIMNOTEK Perairan Darat Tropis di Indonesia, 2024)
Global greenhouse gas levels are significantly impacted by methane emissions from rice fields, especially in Asia, where the majority of the world's rice is produced. This review analyzes research trends on methane emissions from rice fields in East, Southeast, and South Asia, focusing on factors influencing emissions and the effectiveness of mitigation strategies. We synthesized data about 169 papers published between 2000 and 2023 from Web of Science and Google Scholar were merged in Mendeley. The results were visualized using VOSviewer. It covers key aspects such as water management, soil types, farming practices, and rice varieties. Our findings suggest that water management practices, including intermittent drainage and pulse irrigation, play a critical role in reducing methane emissions. Variations in emissions levels are also influenced by soil types, farming practices, and rice varieties. The research highlights significant regional differences, with China and Indonesia being major contributors to emissions, while countries such as Japan and South Korea have implemented effective mitigation measures. Emerging research topics include the impact of organic matter inputs and innovative rice cultivars on emission levels. This review underscores the need for region-specific strategies and research in less studied, such as rainfed and peatland rice fields, to enhance global understanding and control of methane emissions from rice cultivation. The boundary of this review is this manuscript only focusing on methane emissions in artificial wetlands such as rice field area not other water bodies, therefore, further research review in other freshwater ecosystems is encouraged to be done.